Identification and partial characterization of new antigens from simian virus 40-transformed mouse cells. - Chang, C (1979)
Two new species of antigens were detected in simian virus 40-transformed mouse cells, in addition to the large (94,000 daltons) and small (20,000 daltons) tumor antigens. These antigens were immunoprecipitated from cell extracts by using anti-T serum and not normal, nonimmune serum. One of these was a protein with a molecular weight of approximately 130,000 and was present in some but not all SV40-transformed mouse cells. The other, which we have named Tau antigen, has a molecular weight of 56,000 as estimated by electrophoresis through acrylamide gels and was found in all virus-transformed cells examined. The 13,000-daltons antigen contained about 15 methionine-tryptic peptides which were also present in the large SV40 tumor antigen as determined by ion-exchange chromatography. This strongly suggested that the protein was virus coded. The 56,000-dalton Tau antigen appeared to share only two methionine-tryptic peptides with the large species of SV40 tumor antigen, as determined by ion-exchange and paper chromatographies. Our results are compatible with a cellular origin for Tau antigen. However, our data do not exclude the possibility that this protein contains sequences specified by the virus DNA.